Congenital malformations and maternal occupation in Finland: multivariate analysis. Issue 1 (March 1981) - Hemminki, K; Mutanen, P; Saloniemi, I; Luoma, K
Abstract : The Finnish Register of Congenital Malformations was used in a multivariate analysis to explore the associations between maternal occupation in industry and children born with central nervous system (CNS) or musculoskeletal or oral cleft malformations. Possible confounding factors were selected in preliminary screening of risk indicators for malformations. These factors included characteristics of the mother, the child, and the family; maternal illnesses; an maternal medication at the time of pregnancy. Tobacco smoking was a confounding factor for all type of malformations; number of children born to the mother, maternal age, malformations in the family, number of rooms occupied by the family, sex of the child, threatened abortion, and continuous medication of the mother during the first trimester confounded the association for certain type of malformations. After adjusting for confounding factors, maternal occupation in industrial trades significantly correlated with CNS, oral cleft, and musculoskeletal malformation in the offspring. Maternal occupation in industry and construction only was significantly associated with CNS malformations in the offspring but the associations with oral cleft and musculoskeletal malformations were not significant.